Institutional trust as a driver of product boycotts in Europe - Baptista. N.; Dos-Santos, M.; Mata, F.; Jesus-Silva, N. (International Review on Public and Nonprofit Marketing, 2024)
Despite the significant growth in consumer boycotts, research has devoted insufficient attention to the institutional factors that may motivate consumers to engage in such behaviour. This article aims to address this research gap. The main objective is to analyse the factors that affect consumer boycotts from an institutional sustainability perspective, by focusing on a specific dimension of institutional sustainability: institutional trust. Information and data came from the 2023 round of the European Social Survey, a cross-national survey covering 25 Countries. The article applies a binomial univariable logit model to test the influence of institutional trust and other potential drivers on boycott decisions and a multivariable binomial logistic regression to explore possible interrelationship between independent variables. The results confirm that boycotts are affected by institutional trust and other factors including demographic and socio-economic characteristics of the consumers, consumers’ perception of ICT, satisfaction with public institutions, and consumers’ evaluation of personal well-being. This article contributes to political consumerism literature by focusing on the impact of institutional trust in boycotting behaviour. This relationship is underexplored in existing literature, since most literature researches consumer boycotts from a triple-bottom perspective and neglects the effects of the institutional dimension of sustainability in consumer behaviour. The article brings new insights into the motivations of consumers at the political and institutional levels and opens new directions for future research to explore institutional sustainability related to the good practices of governance.